GROWTH PERFORMANCE AND IMMUNE RESPONSE OF SILVER POMPANO SEEDS (Trachinotus blocii) FED WITH FEED CONTAINING IMMUNOSTIMULANT SUPPLEMENTS - Herno Minjoyo; Arief Prihaningrum; Arief Rahman Rivaie; Verly Dharmawanti (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2021)
The increase of the growth performance and control of disease can be done by the use of imunostimulan. Immunostimulant is a material that capable of increasing the non-specific immune response of fish. The purpose of this study was to determine the best concentration of immunostimulants in self-formulated pellet feed on the growth performance and immune response of silver pompano fingerling. The immunostimulant content used it was sourced from commercial products Nutricell. There was three concentrations of imunostimulan were used in this study, namely 0.3% (treatment A), 0.5% (treatment B), and 0,0% (treatment K) and one group fish fed with commercial feed as the control and a comparison (treatment P). A total of 840 silver pompano fish seeds with an average initial body weight of 11,13± 1,39 g were kept in 12 cages (0.8 x 0.8 x 0.6 m3) for 30 days. The results showed that the provision of feed supplements containing commercial immunostimulants did not significantly affect the growth rate, The feed conversion and survival rate but produced the highest total leukocyte count of 65,775. x 10. cells/ml and 35.10% phagocytosis rate achieved on the 30th day of treatment. The results of the five-day challenge test showed that treatment A which was the addition of 0.3% immunostimulant feed had lower mortality than other treatments, after being injected with Vibrio alginolyticus bacteria at a dose of 3 x 109 cfu/ml/0.002 g/head fish weight. Based on the results above, it can be concluded that the formulated feed in treatment A which was added with immunostimulant 0.3% (0.7% total in the feed formula) showed a higher survival performance in the nursery phase of silver pompano fish compared to other treatments.